Additive manufacturing of phosphate glass / polylactic acid composites for biomedical application - He, Lizhe (2021)
Phosphate glass/polylactic acid (PG/PLA) composites are prospective materials for biodegradable bone fracture fixation plates as well as bone tissue engineering scaffolds. However, the PG/PLA composites previously fabricated do not have either the geometry that precisely matches the bone anatomy or the interconnected porous structure that favours the colonisation of bone-forming cells. This work explores the additive manufacturing of PG/PLA composites via fused deposition modelling (FDM). PG in the form of particles (PGP) and milled fibres (PGF) were incorporated into PLA, and then melt-extruded into filament feedstocks for FDM. The FDM-fabricated composites were first studied for their potential for bone fracture fixation devices. Incorporation of PGP or PGF led to reduced flexural strength but increased flexural modulus of composites. Comparing to PGP, the PGF was more effective to improve the flexural modulus, and the resultant composites showed better resistance to in-vitro degradation. The PGF reinforced composites had mechanical properties comparable to biodegradable fixation devices used in clinical practice. The filament preparation process had a strong impact on the length of fibres in FDM products. The longer fibres preserved in FDM products also elicited a higher degree of alignment with the direction of material extrusion during FDM. The fibre alignment and fibre length collectively enhanced the mechanical properties of composites. The FDM-fabricated composites were also investigated as bone tissue engineering scaffolds. The incorporation of PG reinforcement led to enhanced compressive properties and increased surface roughness. However, the strong acidity due to locally accumulated acidic degradation products may result in inferior viability of osteoblast-like cells comparing to PLA-only scaffolds. MgO was added to the PGF/PLA composites as a buffering agent. Its incorporation led to slightly reduced compressive properties, but enhanced surface hydrophilicity. The resultant composite scaffolds did not induce significant acidification of the degradation environment within 14 days of degradation. MgO was extensively degraded to neutralise the acidity, meanwhile preventing the acidity-induced accelerated degradation of PGF. The current project has developed the processes including material preparation, feedstock making and configuration of the FDM process. These processes are all essential to the research of additive manufacturing of PG/PLA composites. The current research shows good prospect for the making of both patient-specific, biodegradable bone fracture fixation plates as well as bone tissue engineering scaffolds with well-defined interconnecting porosity. Further works are required to validate the performances in the context of biomechanical loading and biological testing.